Integrated Process for Ballot Bin Waste Valorization for High-Quality Cellulose Acetate Recovery - Niccolò Lamanna; Giovanni Zuccante; Massimiliano Rossetti; Andrea Franzetti; Carlo Santoro; Luca Zoia (Applied Sciences)
Cigarette butt littering poses a significant environmental challenge, with billions of butts discarded each year, fouling ecosystems with slow-to-decompose cellulose acetate filters that absorb and release harmful compounds. In response, an innovative, sustainable approach for valorizing ballot bin waste (BBW) by extracting high-quality cellulose acetate from cigarette butts was investigated. This green approach eliminates the need for hazardous acids and toxic solvents, resulting in a yield of 30% (w/w) and a degree of substitution (DS) of 2.0–2.5, which is comparable to pure cellulose acetate. The following four essential processes are involved in this process: filter separation, water washing to remove impurities, ethanol purification, and acetone precipitation of the cellulose acetate. This approach not only mitigates environmental harm, but also supports circular economy goals by transforming waste into valuable resources.